An evaluation of the appropriateness of the course book “Family and Friends 4” for primary school learners in Sunshine English School = Sử dụng đọc rộng có hướng dẫn nhằm cải thiện việc học từ vựng ngẫu nhiện cho sinh viên chuyên tiếng Anh năm thứ nhất tạ - Nguyễn, Thị Bích Hạnh (University of Languages and International Studies, 2017)
The study aimed to examine whether EFL extensivereading could lead to increaseincidental vocabulary of elementary-level EFL learnersand evaluate the learners‟ opinionsaboutthe ER program.The participants were 25 freshmen majored in English at Hung Yen Teachers‟ Training College. They were asked to read 6 graded readers within a twelve-weekEFL extensive reading program. The vocabulary pretest and posttests were administered to measure learners‟ incidental vocabulary learning gains in the 118selected target words achieved through the program. Results revealed that the significant vocabulary gains were achieved by the participants after the EFL extensive, eading program, uggesting that the EFL extensive reading treatment had produced a beneficial effect onthe incidental word learning gains of the participants with elementary EFL competence.